Peranan Guru PPKn dalam Menanamkan Nilai- Nilai Patriotisme di SMP Negeri 1 Painan - Wulandari, Nining (Jurnal Ilmu Hukum, Humaniora dan Politik, 2023)
This research aims to describe the role of teachers in instilling patriotism values, identify the obstacles faced by teachers in instilling patriotism values, and identify the efforts made by PPKN teachers in instilling patriotism values at SMP Negeri 1 Painan. The type of research used in this research is qualitative with descriptive methods. The types of data are primary data and secondary data collected through interviews and documentation studies. Data validity testing was carried out through triangulation techniques based on sources. Data analysis was carried out using the process of collecting data in qualitative research, reducing data, presenting data, and drawing conclusions obtained during the research. The results of the research show that the role of PPKn teachers in instilling the values of patriotism has not been fully implemented, this can be seen by the fact that there are still students who do not heed the values of patriotism, such as the discovery of a lack of attitude of love for the homeland of students seen during the flag ceremony, many students are not serious. and considering the flag ceremony as an unimportant activity, what is even more worrying is that there are students who do not memorize the mandatory Indonesian Raya song, this clearly shows the lack of love for the water in the students.